2017
DOI: 10.18203/2320-1770.ijrcog20175824
|View full text |Cite
|
Sign up to set email alerts
|

Carbetocin versus Oxytocin and Misoprostol in prevention of atonic post-partum hemorrhage in high risk patients planed for cesarean delivery

Abstract: Background: Post-partum hemorrhage prevention (PPH) is considered a major issue due to its effect on maternal morbidity and mortality. The objective of this study was to compare efficacy of Carbetocin in prevention of atonic post-partum hemorrhage in high risk patients undergoing elective caesarean section in comparison to Oxytocin and Misoprostol.Methods: 150 pregnant women prepared for elective caesarean section were classified into 3 groups; Group I (50 patients received Carbetocin 100 mg I.V infusion), Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
3
4
0
Order By: Relevance
“…This can be explained by the less number of patients with uterine atony in carbetocin group. This was in agreement with Ali AE-NAE-G et al (2017 ) who found that carbetocin decreases the need for blood transfusion after cesarean [18] . Also, uterine atony which was more significant in the misoprostol group necessitate use of more oxytocin, this agrees with (Sull, Chong YS, Samuel M 200) who concluded that carbetocin significantly decreases the need for other uterotonic drugs [19] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This can be explained by the less number of patients with uterine atony in carbetocin group. This was in agreement with Ali AE-NAE-G et al (2017 ) who found that carbetocin decreases the need for blood transfusion after cesarean [18] . Also, uterine atony which was more significant in the misoprostol group necessitate use of more oxytocin, this agrees with (Sull, Chong YS, Samuel M 200) who concluded that carbetocin significantly decreases the need for other uterotonic drugs [19] .…”
Section: Discussionsupporting
confidence: 91%
“…Uterine atony which was more significant in the misoprostol group necessitate additional surgical procedure to control bleeding such as uterine artery ligation in 3 (2%) patients and uterine compression sutures in 8 (11%) patients. This is in agreement with Ali AE-NAE-G et al (2017) who found that carbetocin decreases the need for surgical measures to decrease blood loss during operation [18] .…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the need for blood transfusion was significantly lower in the carbetocin group. This was in agreement with Ali et al [25] and Moustafa et al [17] who found that carbetocin decreases the need for blood transfusion after cesarean.…”
Section: Discussionsupporting
confidence: 92%
“…In the current research there is no statistically substantial variance (p-value > 0.05) among studied groups with respect to post-partum HCT. In a study done by Ali et al 1 , that was performed to evaluate the efficacy of Carbetocin relative to Oxytocinin in the avoidance of atonic post-partum hemorrhage in high-danger sufferers experiencing optional caesarean section and misoprodtol, hematocrit value assessment preoperative and 48 hours postoperatively after elective cesarean delivery had a mildly substantial disparity among the three groups studied (p <0.05)…”
Section: Baselinementioning
confidence: 99%